Kebon Empring Market as Tourism Potential in Srimulyo Village - Pramusiwi, Aloysia Desy (Jurnal Atma Inovasia, 2022)
Srimulyo Village is located in Piyungan District, Bantul Regency, Special Region of Yogyakarta. By using the service method, various potentials can be obtained such as agriculture, plantations, animal husbandry, and tourism. In agriculture, land use in the southern part of Srimulyo village is dominated by dry land agriculture, while the northern part is dominated by wetland agriculture in the form of irrigated rice fields. The main commodities of dry land agriculture in Srimulyo Village are secondary crops, while the main commodities of wetland agriculture in Srimulyo Village are rice and secondary crops. In the plantation sector, Srimulyo village produces guava, mango, rambutan, banana, and papaya. In addition to fruit, vegetables produced in Srimulyo Village include chili, long beans, onions, spinach, and so on. Srimulyo Village also has village potential in the form of its natural beauty in the tourism sector, such as Watu Amben Hill, Bukit Bintang, and Kebon Empring Market. The author also uses livestock manure to become compost, which is one of the potentials in the field of animal husbandry. It is hoped that the writing of this journal can be useful especially for the development of Srimulyo Village.